1980
DOI: 10.1002/jez.1402120107
|View full text |Cite
|
Sign up to set email alerts
|

Surgical removal of the olfactory bulbs increases sensitivity of the reproductive system of female rats to the inhibitory effects of late afternoon melatonin injections

Abstract: In rats, anosmia induced by olfactory bulbectomy sensitizes the neuroendocrine-reproductive axis to the inhibitory effects of the pineal gland. Thus, combined blinding (which stimulates pineal antigonadotrophic activity) and anosmia cause a marked delay in the sexual maturation of female rats. The present study tested whether anosmia would also sensitize the neuroendocrine axis to the reproductive inhibitory effects of melatonin. In the present study, young female rats were rendered anosmic and maintained unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…These data differ somewhat from those of Chik et al (1987b), who observed significant increases in circulating melatonin concentrations following isoproterenol treatment in both control and underfed rats, with the rise in melatonin occurring more gradually in underfed rats. Chik et al (1987b) Nocturnal secretion of melatonin provides animals with both a circadian and circa-annual message that provides a means of timing daily and seasonal events (Reiter 1991 Evidence from studies on the laboratory rat indicates that under certain conditions, including anosmia (Reiter et al 1980) and food restriction (Sorrentino et al 1971), this normally nonphotoperiodic species may be rendered reproductively photoresponsive. Circulating melatonin concentrations are increased in underfed rats (Chik et al 1987a), and the response to a p-agonist is also altered by underfeeding (Chik et al 1987b …”
Section: Dlscusslonmentioning
confidence: 99%
“…These data differ somewhat from those of Chik et al (1987b), who observed significant increases in circulating melatonin concentrations following isoproterenol treatment in both control and underfed rats, with the rise in melatonin occurring more gradually in underfed rats. Chik et al (1987b) Nocturnal secretion of melatonin provides animals with both a circadian and circa-annual message that provides a means of timing daily and seasonal events (Reiter 1991 Evidence from studies on the laboratory rat indicates that under certain conditions, including anosmia (Reiter et al 1980) and food restriction (Sorrentino et al 1971), this normally nonphotoperiodic species may be rendered reproductively photoresponsive. Circulating melatonin concentrations are increased in underfed rats (Chik et al 1987a), and the response to a p-agonist is also altered by underfeeding (Chik et al 1987b …”
Section: Dlscusslonmentioning
confidence: 99%
“…play an important regulatory role in the diur nal rhythms of biological responses to mela tonin during certain periods of the day in hamsters [8], white-footed mice [36], rats [7] and sheep [37], However, Weaver et al [38] showed that both the melatonin-sensitive and nonsensitive species of mice have similar quality of [125I]iodomelatonin binding sites. The same condition was found in rats and hamsters which have the same amount of [l35l]iodomelatonin binding sites but differ ent melatonin sensitivities demonstrated by their reproductive system [39].…”
Section: Effects O F Melatonin Administration On Serum Melatonin Levementioning
confidence: 99%
“…3], Pineal melatonin secretion has a very pronounced circadian rhythm with a high level in the dark period in all species studied [4], There is also a prominent diurnal variation in the biological response to melatonin [5], The late photophase melatonin administration has been shown to be critical for the melatonin effects on the hypothalamo-pituitary-gonadal systems in an imals [6][7][8][9]. It has been suggested that the sen sitivity of melatonin receptors may play an important role in the diurnal changes of re sponsiveness of melatonin action [7.…”
mentioning
confidence: 99%
“…The circadian rhythmicity of [l25I]melatonin binding in this and other tissues [32] may play an important regulatory role in the diurnal rhythms of responses to melatonin during certain periods of the day in hamsters [33] and rats [34]. However, several authors have shown that the melatonin sensitivity of the species is not related to quantity of [125I]melatonin binding sites [35], suggesting that the increased sensitivity to melatonin in animals is probably due to a difference in a postreceptor mechanism rather than to a dif ference in the density or affinity of the recep tors.…”
Section: Effect Of Castration On [125l]melatonin Binding By the Hardementioning
confidence: 99%